Probabilistic tsunami hazard analysis for Tuzla test site using Monte Carlo simulations - Bayraktar, Hafize Basak. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2018., 2018)
In this study, time-dependent probabilistic tsunami hazard analysis (PTHA) is performed for Tuzla in the Sea of Marmara, Turkey, related to the possible rupture of Prince Island Fault within next 50, 100, 500 and 1000 years. The study associates the probabilistic seismic hazard analysis with tsunami numerical modelling. Synthetic earthquake catalogue, which includes 100 events, was generated by Monte Carlo (MC) simulation technique. This catalogue includes earthquakes having magnitudes between Mw 6.5 and 7.1 (that comes from the maximum moment magnitude range this fault system can generate), of which probability of occurrence and associated tsunami wave heights are calculated. Tsunami numerical code NAMI DANCE using Non-Linear Shallow Water Equations are used for tsunami simulations. According to results of the tsunami numerical modelling, distribution of probability of occurrence with respect to minimum and maximum water surface elevations and maximum ow depth on land are represented. Moreover, tsunami inundation maps of Tuzla region are prepared with regard to probability of exceedance of 0.3 m ow depth and probability of exceedance of 0.3 m tsunami wave heights at synthetic gauge points for di erent time scales. This was observed that tsunami wave heights up to 1 m have 65% probability of exceedance for 50 years return period and this value reaches up to 85% in Tuzla region for next 100 year. Inundation depth also exceeds 1m in Tuzla region with probabilities of occurrence of 60% and 80% for next 50 and 100 years, respectively. When return period increases by 500 and 1000 years, earthquake occurrences demonstrate very high probabilities. Furthermore, inundation maps show that the probability of occurrence of certain ow depths ranges between 10% and 75% when exceedance threshold of wave height considered as 0.3 m for 50 and 100-year time exposure. The maximum inundation distance calculated among entire earthquake catalogue is 60 m in this test site. Looking at the situation for the synthetic gauge points, only few of them has a probability between 75% - 85% when probability of exceedance of 0.3 m wave height is considered for next 50 years and this probability value increases up to 90% for 100-year exposure time. Probabilities are observed more than 95% for 500 and 1000-year return periods due to the short return periods of characteristic faults in Marmara Sea.
Keywords: Tsunami hazard zones.; Tsunamis -- Turkey -- Tuzla.; Tsunamis -- Mathematical models.; Monte Carlo method.